From Nurturing the Successor to Attracting New Founders: How Firm Platforms Organize a Market for Selling Businesses - Stamm Isabell K. (Journal of Organizational Sociology)
Firm platforms organize a market for selling Mittelstand firms in Germany. In doing so they face a challenge: to instill a market frame in a segment of the German economy that is known for its family embedding. This study examines the strategies firm platforms use to reframe ownership transfer from a gift passed on within the family to a commodity traded on a market. Building on a content analysis of the seven largest and most innovative firm platforms in Germany, this study reveals how firm platforms argue from within a gift exchange frame and shift its parameters in social, object, and time dimensions. This study makes a more general point by arguing that digital platforms function as cultural trailblazers in marketization. This study contributes to succession, digital platform, and marketization debates.